Diversity of Rickettsiales bacteria in five species of ticks collected from Jinzhai County, Anhui Province, China in 2021–2022 - Jin, Xiaojing; Liao, Jiasheng; Chen, Qingqing; Ding, Junfei; Chang, Hongwei; Lyu, Yong; Yu, Liang; Wen, Bohai; Sun, Yong; Qin, Tian (Frontiers in Microbiology, 2023)
The order Rickettsiales in the class Alphaproteobacteria comprises vector-borne pathogens of both medical and veterinary importance. Ticks, as a group, are second only to mosquitoes as vectors of pathogens to humans, playing a critical role in the transmission of rickettsiosis. In the present study, 880 ticks collected from Jinzhai County, Lu'an City, Anhui Province, China in 2021–2022 were identified as belonging to five species from three genera. DNA extracted from individual ticks was examined using nested polymerase chain reaction targeting the 16S rRNA gene (rrs), and the gene fragments amplified were sequenced to detect and identify Rickettsiales bacteria in the ticks. For further identification, the rrs-positive tick samples were further amplified by PCR targeting the gltA and groEL gene and sequenced. As a result, 13 Rickettsiales species belonging to the genera Rickettsia, Anaplasma, and Ehrlichia were detected, including three tentative species of Ehrlichia. Our results reveal the extensive diversity of Rickettsiales bacteria in ticks from Jinzhai County, Anhui Province. There, emerging rickettsial species may be pathogenic and cause under-recognized diseases. Detection of several pathogens in ticks that are closely related to human diseases may indicate a potential risk of infection in humans. Therefore, additional studies to assess the potential public health risks of the Rickettsiales pathogens identified in the present study are warranted.